Ukuran Perusahaan Memoderasi Pengaruh Profitability dan Capital Intensity terhadap Tax Avoidance - Dewi, Ni Kadek Karisma; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 33 No 8 (2023), 2023)
The aim of this research is to empirically prove profitability and capital intensity which influence tax avoidance with company size as a moderating variable. Manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021 were selected as the population in this study. Data in the study were analyzed using multiple linear regression analysis techniques and moderated regression analysis. The results of the research conducted show that profitability has a negative effect on tax avoidance. Capital intensity has a negative effect on tax avoidance. Empirically, the effect of profitability on tax avoidance can be strengthened by company size. The effect of capital intensity on tax avoidance cannot be strengthened by company size. Keywords: Profitability; Capital Intensity; Firm Size; Tax Avoidance.